From protest to president : a social justice journey through the emergence of adult education and the birth of distance learning - Pruitt, George A., 1946- (Rutgers University Press, 2023)
"From Protest to President describes an inspirational odyssey of a young, Black activist coming of age in Mississippi and Chicago in the tumultuous 1960s and '70s, culminating in a notable thirty-five-year presidency at Thomas Edison State University. From barbershop encounters with Malcolm X to death threats at Illinois State University and gunfire at Towson State, Pruitt provides a powerful narrative poised at the intersection of social justice, higher education and politics. He recounts leadership experiences at HBCUs and public universities across the country, as he advocated for autonomy at Morgan State and fought to preserve Tennessee State University. His steadfast activism, integrity and courage led to groundbreaking work in providing access to higher education for working adults and the military. From his days as a student protester in high school and college to his appearances on Capitol Hill, Pruitt has earned the reputation as a candid and influential leader in higher education."--